2013
DOI: 10.1007/s00414-013-0876-x
|View full text |Cite
|
Sign up to set email alerts
|

Markers of mechanical asphyxia: immunohistochemical study on autoptic lung tissues

Abstract: Forensic pathologists are often asked to provide evidence of asphyxia death in the trial and a histological marker of asphyxiation would be of great help. Data from the literature indicate that the reaction of lung tissue cells to asphyxia may be of more interest for forensic purposes than migrating cells. The lungs of 62 medico-legal autopsy cases, 34 acute mechanical asphyxia (AMA), and 28 control cases (CC), were immunostained with anti-P-selectin, anti-E-selectin, anti-SP-A, and anti-HIF1-α antibodies, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…); in the lungs in cases of mechanical asphyxia (Cecchi et al. ); and in the kidneys, especially in cases of acute circulatory failure (Zhao et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…); in the lungs in cases of mechanical asphyxia (Cecchi et al. ); and in the kidneys, especially in cases of acute circulatory failure (Zhao et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HIF expression has been related to different causes of death in different organs, specific targets of hypoxia. In particular, increases in HIF expression have been observed: in myocardial tissue in cases of myocardial ischaemia (Blanco Pamp ın et al 2006) or cardiac death (Zhu et al 2008); in the lungs in cases of mechanical asphyxia (Cecchi et al 2014); and in the kidneys, especially in cases of acute circulatory failure (Zhao et al 2006). However, to the best of our knowledge, gingival tissue is not a specific target of hypoxia in the peri mortem period; thus, there is no reason to hypothesize a different pattern of hypoxia related to HIF-1a expression in gingival tissue that is associated with a specific cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…And an increase of SP-A in mechanical asphyxia cases demonstrates that hypoxia is the distinguishing feature of death in such cases [24]. In addition, Cecchi et al have demonstrated that HIF-1a (hypoxia-induced factor 1-a), a target of mir-122 expressed in response to hypoxia, was up-regulated in mechanical asphyxia compared with craniocerebral injury, natural death and other causes of death [25, 26]. Our findings thus indicate that mir-122 reduction might be the response to hypoxia in mechanical asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is produced by type II alveolar cells and physiologically lines the alveoli and smallest bronchioles. As it is the major surfactant protein, its deficiency causes respiratory distress [19][20]. Hypoxia increases its production, causing its precipitation and formation of aggregates of SP-A in the alveolar spaces, likely due to the exertions of forced breathing [20].…”
Section: Introductionmentioning
confidence: 99%